Lost & found : unlocking collaboration and compassion to help our most vulnerable, misunderstood students (and all the rest) - Greene, Ross W. (J-B Ed: reach and teach, 2021)
"An astonishing 62% of teachers who have been teaching in the same school for 5 years report that behavior issues that interfere with teaching and learning have notably worsened. In response to this ever-growing issue, Ross Greene's groundbreaking Collaborative Problem Solving approach helps educators understand and help behaviorally challenging kids. With CPS, adults understand that behavioral challenges stem from lagging skills in the domains of flexibility/adaptability, frustration tolerance, and problem solving. CPS represents a more compassionate productive approach to behavioral challenges. Lost & Found, 2nd Edition is a revised and updated guide that builds on renowned psychologist Dr. Ross Greene's landmark works, The Explosive Child and Lost At School. Greene provides educators with concrete steps to using CPS with students and bring attention to the shortcomings of traditional school discipline. The advice in the book is based upon Dr. Greene's vast experience of implementing the technique into schools and accounts of others who have proven the success of the technique. The new edition will feature updated examples and dialogues intended for modern-day classrooms, innovative approaches from his constantly evolving model, and other recent behavioral studies"--